Constitutional Review Mechanisms for Village Regulations in Indonesia - Didik Sukriono; Alfan Bramantya; Sudirman Sudirman; Dewi Fortuna Sari; Neola Hestu Prayogo (Unissula, 2026)
This article examines the effectiveness of constitutional control mechanisms applied to village regulations within Indonesia’s statutory system. Although village governments possess regulatory authority under Law Number 6 of 2014 on Villages, ambiguities remain regarding supervision and constitutionality testing of village regulations under Law Number 12 of 2011 and Law Number 23 of 2014. This research employs a socio‑legal study design combining doctrinal legal analysis with empirical field investigation. Empirical data were gathered by document analysis, focus group discussions, and interviews involving village and local administrators in several regencies in East Java. The study analyzes three mechanisms of constitutional control: executive preview and executive review conducted by regency governments, legislative review carried out by village institutions, and judicial review practiced by the Supreme Court. The findings demonstrate that, despite the existence of multiple supervisory mechanisms, their practical implementation remains weak and fragmented. Executive supervision often operates informally, legislative deliberation in villages is frequently less substantive, and judicial review mechanisms are rarely utilized due to limited legal awareness. Consequently, the effectiveness of constitutionality testing of village regulations remains low. This study contributes to constitutional review and decentralization literature by identifying legal and institutional barriers to effective village regulatory oversight.